Optimization of treatment strategies for elderly patients with advanced non-small cell lung cancer - Chen, Qiang; Ying, Shuo; Qin, Jianwen; Zhang, Li (Frontiers in Oncology, 2024)
Lung cancer stands as a malignant neoplasm bearing the highest burden of morbidity and mortality within the elderly population on a global scale. Among the lung cancer subtypes, non-small cell lung cancer (NSCLC) prevails as the most prevalent. As age advances, elderly patients often present with an increased prevalence of comorbidities, diminished organ reserve function, and alterations in drug pharmacokinetics, including absorption, distribution, metabolism, and clearance. These factors collectively contribute to a reduction in their capacity to tolerate therapeutic interventions. Regrettably, there exists a paucity of research data and evidence regarding the management of elderly patients afflicted by advanced lung cancer. This article endeavors to compile and elucidate strategies for the enhancement of treatment approaches, with the aim of aiding clinical decision-making. Prior to the selection of clinical treatment modalities for elderly patients with advanced NSCLC, a comprehensive assessment should be conducted, taking into account various facets, including tumor characteristics, patient age, physiological status, and the presence of comorbidities. The treatment strategy should be implemented in a tiered fashion, thereby affording the opportunity for the tailoring of individualized therapeutic approaches for elderly patients afflicted by advanced NSCLC. The demographic of elderly patients confronting advanced NSCLC presents a complex landscape marked by intricate underlying conditions, necessitating the imperative optimization of treatment strategies.